Do‐or‐die life cycles and diverse post‐infection resistance mechanisms limit the evolution of parasite host ranges. (4th February 2014) - Sieber, Michael; Gudelj, Ivana; Thrall, Peter
Abstract In light of the dynamic nature of parasite host ranges and documented potential for rapid host shifts, the observed high host specificity of most parasites remains an ecological paradox. Different variants of host‐use trade‐offs have become a mainstay of theoretical explanations of the prevalence of host specialism, but empirical evidence for such trade‐offs is rare. We propose an alternative theory based on basic features of the parasite life cycle: host selection and subsequent intrahost replication. We introduce a new concept of effective burst size that accounts for the fact that successful host selection does not guarantee intrahost replication. Our theory makes a general prediction that a parasite will expand its host range if its effective burst size is positive. An in silico model of bacteria‐phage coevolution verifies our predictions and demonstrates that the tendency for relatively narrow host ranges in parasites can be explained even in the absence of trade‐offs.